The corrosion-fatigue measurement test of the Zn-Al alloy coated steel wire. (October 2020) - Xue, Songling; Shen, Ruili; Chen, Wei; Shen, Lilai
Abstract: In this paper, the S-N curve of Zn-Al alloy coated steel wire was obtained by setting 30 groups with different corrosion-fatigue tests. The results show that the corrosion-fatigue resistance of Zn-Al alloy coated steel wire is preferable to high-strength steel wire. The crack initiation time of Zn-Al alloy coated steel wire is longer than high-strength steel wire, and the propagation speed is far lower than high-strength steel wire. Finally, a life prediction model considering corrosion-fatigue coupling effect is proposed. The calculation results show that the model considering corrosion-fatigue coupling effect can reflect the corrosion-fatigue coupling effect to some extent. The correctness of the theory is checked by comparing the calculation results with the experimental results.